The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.2355/isijinternational.isijint-2018-417
|View full text |Cite
|
Sign up to set email alerts
|

Off-line Model of Blast Furnace Liquid Levels

Abstract: An off-line simulation model of the blast furnace hearth is developed based on mass balances for iron and slag, expression of the liquids outflow rates and logical conditions for the start and the end of the outflow of liquids. The dynamic model divides the furnace hearth into two regions of sizes that may change during the tapping process. It provides a description of the time evolution of the liquid levels and predicts the duration and the periods of iron-or slag-only flow in the beginning of the taps. The v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 22 publications
3
23
0
Order By: Relevance
“…The large hearth diameter in multi-taphole blast furnaces may give rise to zones of different coke-bed permeability, which leads to differences in the local conditions and liquid levels [18,19]. A mathematical model was developed by the present authors [14] and applied to study the effect of different parameters and variables on the liquid levels and drainage process. The hearth was modelled as two interconnected pools of liquids, where communication factors can control the flow from one taphole zone to the other.…”
Section: Results Of Pca and Liquid Level Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The large hearth diameter in multi-taphole blast furnaces may give rise to zones of different coke-bed permeability, which leads to differences in the local conditions and liquid levels [18,19]. A mathematical model was developed by the present authors [14] and applied to study the effect of different parameters and variables on the liquid levels and drainage process. The hearth was modelled as two interconnected pools of liquids, where communication factors can control the flow from one taphole zone to the other.…”
Section: Results Of Pca and Liquid Level Modelmentioning
confidence: 99%
“…Several studies in the literature have presented models of hearth drainage [1,2,[10][11][12][13]. A recent study by the present authors proposed a simple offline model simulating the liquid level fluctuations in a hearth with intermittent tapping [14]. By applying different conditions to each taphole, it was demonstrated that some outflow patterns and slag delays observed in a blast furnace could be mimicked.…”
Section: Introductionmentioning
confidence: 90%
“…The initial l-l interface level (above the taphole) is related to the amount of accumulated molten iron in the BF hearth at the commencement of drainage, the dead man porosity, the level of the taphole, and the taphole length. For multi-taphole furnaces, it is also strongly related to the operation of the alternate taphole used [10,12]. The outer level of the taphole is predetermined for every BF, but the angle and the length of the taphole may vary.…”
Section: Influence Of the Initial L-l Interface Levelmentioning
confidence: 99%
“…For drainage of a hearth with a heterogeneous dead man, socalled viscous fingering may occur in the l-g interface close to the taphole [8,9]. Furthermore, for large BFs, it is estimated that the vertical level of the interfaces may vary in different parts of the hearth as a result of an impermeable dead man [10][11][12]. Such special phenomena can make the motion of the interfaces far more complicated than the expected overall behavior outlined above.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation